Influence of the cis-9, cis-12 and cis-15 double bond position in octadecenoic acid (18:1) isomers on the rat FADS2-catalyzed Δ6-desaturation. (April 2015) - Rioux, Vincent; Choque, Benjamin; Ezanno, Hélène; Duby, Cécile; Catheline, Daniel; Legrand, Philippe
Abstract: Oleic ( cis 9-18:1), linoleic ( cis 9, cis 12-18:2) and α-linolenic ( cis 9, cis 12, cis 15-18:3) acids are well described substrates of the Δ6-desaturase encoded by the mammalian fatty acid desaturase 2 (FADS2) gene. In addition, at least 9 other very structurally different fatty acids have been shown to be Δ6- or even Δ8-desaturated by the FADS2 protein. A better characterization of the substrate specificity of this enzyme is therefore needed. By using commercial cis 9-18:1 and chemically synthesized cis 12- and cis 15-18:1 (sharing the n-6 double bond with 18:2 n-6 and the n-3 double bond with 18:3 n-3, respectively), we tried to decrypt the fatty acid structure driving the FADS2 substrate affinity. We first showed that both recombinant and native rat FADS2 were able to Δ6-desaturate not only the cis 9- but also the cis 12- and cis 15-18:1 isomers. Next, the inhibitory effect of increasing concentrations of each 18:1 isomer was investigated in vitro on the Δ6-desaturation of α-linolenic acid. At equimolar inhibitor/substrate ratio (60 μM), the cis 9-18:1 exhibited a significantly higher inhibition (25%) than the cis 12- (8%) and cis 15-18:1 (5%). This study shows that a single cis double bond in 12- or 15-position in 18:1 is enough to make them low Δ6-desaturable substrates. If a preexisting cis 9-double bond is not absolutely required for the Δ6-desaturation of octadecenoic acids, its presence is however crucial to explain the higher enzyme affinity. Compared with oleic acid, the additional presence of a cis 12-double bond in linoleic acid increased its inhibitory effect on the Δ6-desaturation of α-linolenic acid at low concentration (30 μM) but not at higher concentrations (60 and 120 μM). In this classification of the decreasing impact of the double bond when it comes closer to the methyl end of octadecenoic acids, the cis 11-18:1 ( cis -vaccenic acid) should be considered apart since it is itself not Δ6-desaturated but still a good competitive inhibitor of the α-linolenic acid Δ6-desaturation.